No Evidence for Dystonia-Like Sensory Overflow of Tongue Representations in Adults Who Stutter - Vreeswijk, Sarah M. E.; Hoang, T. N. Linh; Korzeczek, Alexandra; Neef, Nicole E.; Wolff von Gudenberg, Alexander; Paulus, Walter; Sommer, Martin (Frontiers in Human Neuroscience, 2019)
Persistent developmental stuttering (PDS) disrupts speech fluency in about 1% of adults. Although many models of speech production assume an intact sensory feedback from the speech organs to the brain, very little is actually known about the integrity of their sensory representation in PDS. Here, we studied somatosensory evoked potentials (SEPs) in adults who stutter (AWS), with the aim of probing the integrity of sensory pathways. In addition, we tested the processing of dual sensory input to address a putative link between stuttering and focal dystonia. In 15 AWS (aged 15–55 years; three females) and 14 matched fluent speaking adults (ANS), we recorded SEPs at C5′ and C6′ induced by stimulating separately or simultaneously the tongue or the cheek at the corner of the mouth. We determined latencies (N13, P19, and N27) and peak-to-peak amplitudes (N13-P19, P19-N27). We divided amplitudes from simultaneous stimulation by the sum of those from separate stimulation. Amplitude ratios did not differ between groups, indicating normal processing of dual sensory input. This does not support a clinical analogy between focal dystonia and persistent stuttering. SEP latencies as a measure of transmission speed in sensory pathways were significantly shorter in stuttering subjects than in fluent speaking participants, however, this might have been related to a trend for a height difference between groups, and was not confirmed in a replication dataset. In summary, we did not find evidence for dystonia-like sensory overflow of tongue representations in AWS.